Odpowiedź :
Szczegółowe wyjaśnienie:
a) 2x - 3x = 9
-x = 9
x = -9
f) 3x - 5 - x = 11
3x - x = 16
2x = 16
x = 8
g) x - 5 + 6x = 16
x + 6x = 21
7x = 21
x = 3
h) 3x - 4 - 2x = 16
3x - 2x = 20
x = 20
Odpowiedź:
e)
[tex]2x - 3 + x = 9[/tex]
[tex]2x + x = 9 + 3[/tex]
[tex]3x = 12[/tex]
[tex]x = 4[/tex]
f)
[tex]3x - 5 - x = 11[/tex]
[tex]3x - x = 11 + 5[/tex]
[tex]2x = 16[/tex]
[tex]x = 8[/tex]
g)
[tex]x - 5 + 6x = 16[/tex]
[tex]x + 6x = 16 + 5[/tex]
[tex]7x = 21[/tex]
[tex]x = 3[/tex]
h)
[tex]3x - 4 - 2x = 16[/tex]
[tex]3x - 2x = 16 + 4[/tex]
[tex]x = 20[/tex]
Pozdrawiam i miłego dnia :)